Functional nanostructured oxides. (April 2015) - Maaza, M.; Ngom, B.D.; Achouri, M.; Manikandan, K.
Abstract: This contribution reports on novel physical properties of specific oxides in their nano scaled configuration. This includes the ultrafast optical limiting of VO2 thin films, the magneto-optical tunability of the ESR response of α-Cr2 O3 nano-spheres, and the reversible control of the surface tension of ZnO oriented nano-rods as well as the validation of the synthesis of high crystalline stoichiometric of rare earth nanostructures by the so called local gas feeding beam pulsed laser deposition. Highlights: Photo-induced and photo-tunable phenomena in nano-structured oxides are reported. VO2 nano-coating exhibit ultrafast optical limiting. α-Cr2 O3 nano-spheres exhibit magneto-optical tunability and enhanced ESR response. ZnO oriented nano-rods exhibit reversible photo-controlled the surface tension. High crystalline RE2O3 nanostructures by local gas feeding/pulsed laser deposition.